PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN WISATAWAN DI DERAWAN FISHERIES COTTAGE PULAU DERAWAN - Ingglade Janely Parengga; I Ketut Suwena; Ni Putu Eka Mahadewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
This exotic Derawan Island has enchanting natural beauty, especially marine tourism so that it can attract tourists both domestically and abroad. Then there was the Covid-19 Pandemic which had a bad impact on the Derawan Island tourism industry such as restaurants, watersport rentals, souvenir shops, especially on accommodation entrepreneurs. The level of tourist visits is decreasing, also impacting the decline in room occupancy rates as experienced by Derawan Fisheries Cottage. To be able to continue to compete in this field, the quality of services and tourist facilities must be continuously improved in addition to providing tourist satisfaction, as well as to create a good image in the eyes of tourists. The purpose of this study is to find out the characteristics and influence of variable quality of services and tourist facilities on the satisfaction of tourists staying at Derawan Fisheries Cottage. This study used a sample of 100 respondents with a sampling technique is purposive sampling. The data in this study was taken with observation techniques, questionnaires, interviews and literature studies. The data is analyzed using multiple linear regressions, hypothesis tests and classical assumption tests. The results concluded that there is a partial and simultaneous significant influence between the quality of services and tourist facilities on tourists staying at Derawan Fisheries Cottage. This is evidenced by the results of the simultaneously obtained a Fhitung value of 42,796 > Ftabel which is 2.70 with a significance of 0.000.